Optimizing the Curriculum of Religious Education and Ethics Based on Deep Learning in Improving Students' Critical Thinking Skills at Islamic Boarding Schools - Fika Abidah Erdelia; Iman Fadilah; Fitria Martanti (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2026)
The research aims to identify the need for curriculum implementation, analyze the obstacles to the implementation of deep learning, and explore adaptive curriculum development strategies in improving students' critical thinking skills in the context of the Independent Curriculum and pesantren values. This research is here to fill the limitations of previous studies that have not discussed the integration of deep learning approaches in the curriculum of religious education in Islamic boarding school-based vocational schools. The research uses a qualitative approach with a case study design at SMK Miftahul Huda Limbangan. The research participants were selected purposively involving PABP teachers, curriculum managers, and students who were directly involved in the implementation of the curriculum. Data were collected through semi-structured interviews, participatory observations, and document analysis in the form of syllabus and teaching modules. To minimize the subjectivity of interpretation, the validity of the data is strengthened through source triangulation, which is comparing the results of interviews, observations, and institutional documents, and analyzed using thematic analysis techniques. The results show that teachers need interactive learning strategy training and flexible curriculum development, while curriculum managers emphasize the importance of contextual teaching materials and external collaboration. Students prefer discussion-based learning methods, educational games, and practical projects. This study also found implementation obstacles that include limited learning time and facilities, learning culture that is still memorization oriented, and teacher readiness and student participation that are not optimal. The research concludes that the optimization of the deep-learning-based PABP curriculum can support the development of more adaptive and participatory Islamic education through teacher capacity building, contextual learning strategies, and project-based assessments relevant to 21st century competencies.